Sustainable Organizations Models, Applications, and New Perspectives - Sánchez-García, Jose C.; Hernández-Sánchez, Brizeida (IntechOpen, 2021)
Given the multidisciplinary nature of our object of study, sustainability, we have divided this book into twelve chapters. In the first four, we cover the content required to learn how to start a business and create companies based on sustainability. The following chapters provide guidance to help translate sustainability strategies across cultures. These processes are analyzed through the Triple Bottom Line perspective, which effectively describes the primary objectives of sustainability. The last chapters analyze current trends in sustainable development, framing education as a powerful tool to facilitate the transition to more sustainable forms of development. Through these chapters, the understanding of the theoretical concepts is facilitated and examples of sustainable enterprises are made available to the reader that serves as a reference and that allow the development of practical activities.